2020
DOI: 10.1007/s00408-020-00392-9
|View full text |Cite
|
Sign up to set email alerts
|

Moderate or Severe Impairment in Pulmonary Function is Associated with Mortality in Sarcoidosis Patients Infected with SARS‑CoV‑2

Abstract: Purpose To investigate whether sarcoidosis patients infected with SARS-CoV-2 are at risk for adverse disease outcomes. Study Design and Methods This retrospective study was conducted in five hospitals within the Mount Sinai Health System during March 1, 2020 to July 29, 2020. All patients diagnosed with COVID-19 were included in the study. We identified sarcoidosis patients who met diagnostic criteria for sarcoidosis according to accepted guidelines. An adverse disease outcome was defined as the presence of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…This is in stark contrast to the 5-10% of the general population that required the same type of support [3]. It is suggested that sarcoidosis patients who present with moderate to severe impairment in pulmonary function have an increased mortality rate due to SARS-CoV-2 infection [1,4].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This is in stark contrast to the 5-10% of the general population that required the same type of support [3]. It is suggested that sarcoidosis patients who present with moderate to severe impairment in pulmonary function have an increased mortality rate due to SARS-CoV-2 infection [1,4].…”
Section: Discussionmentioning
confidence: 98%
“…SARS-CoV-2 related lung disease has resulted in significant morbidity and mortality worldwide [3]. The risk factors for severe SARS-CoV-2 disease include increasing age and comorbidities, with chronic respiratory diseases being among them [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the conclusions across studies are inconsistent. 1 , 2 , 3 , 4 , 5 , 6 Recently, Liu et al. performed a meta-analysis based on six studies with 2091 cases published in Journal of Infection to investigate the association between autoimmune diseases and severe or dead COVID-19.…”
mentioning
confidence: 99%
“…We at LUNG were very selective in our acceptance of SARS-CoV-2-related manuscripts, since most submissions were retrospective, descriptive series of patients, often small in number and not contributing to the extant published literature. Four notable exceptions included the first study reporting an association of COVID-19 outcome with levels of surfactant protein D [ 21 ]; a study of the effect of COVID-19 on patients with sarcoidosis [ 22 ]; a State-of-the-Art review on the relevance of the ACE-2 receptor in SARS-CoV-2 infection [ 14 ]; and an editorial examining chronic cough as a residual effect of the illness [ 23 ].…”
mentioning
confidence: 99%